2017
DOI: 10.19044/esj.2017.c1p5
|View full text |Cite
|
Sign up to set email alerts
|

Potential Alzheimer’s Disease Therapeutics Among Weak Cysteine Protease Inhibitors Exhibit Mechanistic Differences Regarding Extent of Cathepsin B Up-Regulation and Ability to Block Calpain

Abstract: Cysteine protease inhibitors have long been part of drug discovery programs for Alzheimer’s disease (AD), traumatic brain injury (TBI), and other disorders. Select inhibitors reduce accumulating proteins and AD pathology in mouse models. One such compound, Z-Phe-Aladiazomethylketone (PADK), exhibits a very weak IC50 (9–11 μM) towards cathepsin B (CatB), but curiously PADK causes marked up-regulation of the Aβ-degrading CatB and improves spatial memory. Potential therapeutic and weak inhibitor E64d (14 μM IC50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…No difference in exploratory mobility in the maze was evident among the groups of mice (lower graph in Figure 5A). In addition to PADK being linked to cognitive repair, SD1002 from Table 1 also exhibited 83% functional recovery in the AD mouse model (Mann–Whitney test: p = 0.033), and E64d is a compound shown by several studies to improve cognition [27]. From the PADK results, it is noteworthy that a within-animal analysis between percentage increase in hippocampal CatB and the extent of functional recovery found a positive relationship as determined by linear regression ( R = 0.860; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No difference in exploratory mobility in the maze was evident among the groups of mice (lower graph in Figure 5A). In addition to PADK being linked to cognitive repair, SD1002 from Table 1 also exhibited 83% functional recovery in the AD mouse model (Mann–Whitney test: p = 0.033), and E64d is a compound shown by several studies to improve cognition [27]. From the PADK results, it is noteworthy that a within-animal analysis between percentage increase in hippocampal CatB and the extent of functional recovery found a positive relationship as determined by linear regression ( R = 0.860; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…CatB enzymatic activity was assessed in brain sample aliquots using the InnoZyme Cathepsin B Activity Assay Kit (Millipore) as previously described [14,27]. Equal amounts of brain homogenates (10 μg of protein) were assessed in duplicate per sample for proteolytic activity using the Z-Arg-Arg-7-amido-4-methylcoumarin (AMC) substrate and a SpectraMax M3 microplate reader.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of CTSs has been widely explored over the last decades in the field of chronic inflammatory diseases [27,37,204,205], cardiovascular diseases [10,19,181], osteoporosis [70][71][72][73], arthritis [28,206], kidney diseases [30][31][32]84], pancreatitis [207], obesity [208][209][210], cancer [25,34,48,74,82,211], neurodegenerative diseases [39,41,184,185,212,213], and many other pathological states. Multiple inhibitors are currently available, ranging from reversible covalent inhibitors to irreversible inhibitors [214][215][216][217][218] (Table 4).…”
Section: Cathepsin Inhibitors and Their Therapeutic Applicationsmentioning
confidence: 99%
“…Moreover, previous studies reported the involvement of a calcium-activated protease, calpain, in the development of diabetic cardiomyopathy via disrupting ATP synthase and inducing ROS generation (27,28). Calpain activity, measured as ratios of degradation product (BDP145) of αII-spectrin to intact αII-spectrin with and without calcium (29), was enhanced as the Elmo1 expression increased (Supplemental Figure 8D), suggesting some role for calpain in the ELMO1-linked enhancement of cardiomyopathy.…”
Section: Elmo1-mediated Cardiac Production Of Ros Metabolic Dysregulmentioning
confidence: 75%